A importância do armazenamento a nível de propriedade rural - Medina, Cristiane de Conti (Semina: Ciências Agrárias, 1989)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The aim of this work was to identify the main points of choking in the grain comercialization and to demonstrate the importance of the storage at farms. A literature review verified that Brazil stores only 3% of grain at the farms, while in developed countries this type of storage is 60%. The estimate of postharvest waste is 30% of yield, demonstrating the deficiency of the Brazilian storage system.